Tingkat Kepatuhan Masyarakat terhadap Hukum Adat dalam Pernikahan di Nagari Guguk Nunang Kabupaten Lima Puluh Kota - Abbhie Zacky Anggara; Maulid Hariri Gani; Gusneli (STKIP Subang, 2026)
The Minangkabau people are known for their matrilineal kinship system, which regulates social life, including marriage. One customary rule that is still maintained is the prohibition of inter-tribal marriage, because it is considered that kinship ties are still maintained through the maternal line. However, over time, the community began to practice inter-tribal marriages even though they conflict with this customary law. This study uses a qualitative research method with data collection techniques through interviews and observations. Informants in this study consisted of the community and niniak mamak (elderly women) who are familiar with customary marriage rules in Nagari Guguak Nunang. This study aims to determine the form of weakening community compliance with customary law, the factors causing it, and its impact on the community's social life. The results show that the weakening community compliance with customary law is influenced by modernization, developments in education and technology, the influence of migration, the lack of instillation of customary values ​​in the family, and the reduced role of niniak mamak (elderly women) in guiding nieces and nephews. In addition, marriage decisions are currently based more on personal choice than customary considerations. The impacts include the emergence of family conflicts, tension in kinship relations, reduced customary authority, and the erosion of the values ​​of deliberation and togetherness in Minangkabau society.